2012
DOI: 10.1186/1476-7120-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Real-time three-dimensional transthoracic echocardiography in daily practice: initial experience

Abstract: Aim of the workTo evaluate the feasibility and possible additional value of transthoracic real-time three-dimensional echocardiography (RT3D-TTE) for the assessment of cardiac structures as compared to 2D-TTE.Methods320 patients (mean age 45 ± 8.4 years, 75% males) underwent 2D-TTE and RT3D-TTE using 3DQ-Q lab software for offline analysis. Volume quantification and functional assessment was performed in 90 patients for left ventricle and in 20 patients for right ventricle. Assessment of native (112 patients) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…Up to 95% of the authors' cases had echocardiographic guidance, since it plays a crucial role during the procedure and directs the operator during different phases of the intervention, such as choosing the right place for trans-septal puncture, appropriate crossing of the guidewire through the defect, choice of the device, and immediate evaluation of the result, with severity of the leak and its size being best estimated by 3D transesophageal echocardiography. In recent years, new technology of 3D echocardiography images fusion with fluoroscopy has been described to be able to help facilitate the success of the procedure and better assess the result 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Up to 95% of the authors' cases had echocardiographic guidance, since it plays a crucial role during the procedure and directs the operator during different phases of the intervention, such as choosing the right place for trans-septal puncture, appropriate crossing of the guidewire through the defect, choice of the device, and immediate evaluation of the result, with severity of the leak and its size being best estimated by 3D transesophageal echocardiography. In recent years, new technology of 3D echocardiography images fusion with fluoroscopy has been described to be able to help facilitate the success of the procedure and better assess the result 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…20 Meanwhile TTE, the traditional first step for PV evaluation, infrequently images this valve well, especially in adults. 3,6,17,[21][22][23][24][25][26] Three dimensional TTE image continues to evolve and as a result image quality and resolution also continue to improve, but 3D echo remains even more dependent on image quality than 2D echo. 2,23 A previous study showed 59% of patients had sufficient PV imaging by 3D TTE;…”
Section: Discussionmentioning
confidence: 99%
“…The apparent limitations of the RT3DE are largely related to its ongoing development, 28 , 29 specifically, the low rates of frames caused by imperfect translation of data sets and lack of agreement among the various softwares used for 3D evaluation. 30–33 Overall, the RT3DE method has improved image quality from the standard 2D images and measured cardiac function with superior diagnostic accuracy in predicting LV mass, systolic function, along with LV and RV volume when compared with 2DE.…”
Section: Discussionmentioning
confidence: 99%